Protein structure, amino acid composition and sequence determine proteome vulnerability to oxidation‐induced damage. (19th October 2020) - Chang, Roger L; Stanley, Julian A; Robinson, Matthew C; Sher, Joel W; Li, Zhanwen; Chan, Yujia A; Omdahl, Ashton R; Wattiez, Ruddy; Godzik, Adam; Matallana‐Surget, Sabine
Abstract: Oxidative stress alters cell viability, from microorganism irradiation sensitivity to human aging and neurodegeneration. Deleterious effects of protein carbonylation by reactive oxygen species (ROS) make understanding molecular properties determining ROS susceptibility essential. The radiation‐resistant bacterium Deinococcus radiodurans accumulates less carbonylation than sensitive organisms, making it a key model for deciphering properties governing oxidative stress resistance. We integrated shotgun redox proteomics, structural systems biology, and machine learning to resolve properties determining protein damage by γ‐irradiation in Escherichia coli and D. radiodurans at multiple scales. Local accessibility, charge, and lysine enrichment accurately predict ROS susceptibility. Lysine, methionine, and cysteine usage also contribute to ROS resistance of the D. radiodurans proteome. Our model predicts proteome maintenance machinery, and proteins protecting against ROS are more resistant in D. radiodurans . Our findings substantiate that protein‐intrinsic protection impacts oxidative stress resistance, identifying causal molecular properties. Synopsis: Proteins differ in intrinsic vulnerability to carbonylation, an adaptation for oxidative stress tolerance. Here, an integrated proteomics, protein structure, and machine learning approach unravels properties determining damage by γ‐irradiation in two bacterial species at multiple biological scales. γ‐irradiation causes more‐targeted oxidative degradation of proteins in D. radiodurans than in E. coli, suggesting the evolution of protein‐specific protection mechanisms against oxidative stress. D. radiodurans proteins enriched in methionine and cysteine but depleted in lysine are more resistant to oxidative degradation. Protein‐intrinsic molecular properties including local solvent accessibility, electrostatic charge, and lysine enrichment predict site‐specific vulnerability to protein carbonylation by reactive oxygen species in E. coli and D. radiodurans . D. radiodurans ribosomal proteins, chaperones, and proteins involved in response to and detoxification of reactive oxygen species are more resistant to carbonylation than their E. coli orthologs. Abstract : An integrated approach combining redox proteomics, structural systems biology and machine learning resolves molecular properties underlying superior proteome protection in radiation‐resistant Deinococcus radiodurans .